Photo-physico-chemical properties of 1,3-benzenediol-substituted face-to-face phthalocyanines - Canlica, Mevlude (ELSEVIER SCIENCE SA, 2020)
Here, we report the synthesis of new ball-type phthalocyanines that are symmetrically substituted with Mg-Mg, Zn-Zn, and Co-Co centers and contain four 1, 3-benzenediol substituents at the beta positions. The structures and photophysical properties, including the fluorescence quantum yield, triplet quantum yield, and photo-chemical properties with singlet oxygen quantum yield, of these compounds were investigated. Moreover, the applicability of these molecules as photosynthesizers in cancer nanomedicines is discussed. Furthermore, the photodegradation quantum yield of the complexes with the inclusion of Co binuclear phthalocyanine was ex-amined, and their fluorescence and triplet lifetimes were studied in dimethyl sulfoxide. The obtained Uv-Vis spectra exhibited unexpected results; for instance, H2Pc exhibited a broad and peculiar Q band with D4h symmetry. Moreover, H2Pc was found to have a triplet lifetime of 460 mu s whereas ZnPc had a higher triplet lifetime of 1100 mu s.
Keywords: Ball-type phthalocyanine; Face-to-face interaction; Fluorescence quantum yield; Singlet oxygen quantum yield; Triplet life time; OXYGEN QUANTUM YIELDS; METAL-FREE; ZINC PHTHALOCYANINE; PHOTOPHYSICAL PROPERTIES; SENSING PROPERTIES; FLUORESCENCE; SINGLET; 1,2-BIS(3,4-DICYANOPHENOXYMETHYL)BENZENE; METALLOPHTHALOCYANINES; COMPLEXES; Chemistry